Practitioner Note 3: Inclusive communication, case management and accountability - Maya Hammad (International Policy Centre for Inclusive Growth (IPC-IG), 2022)
This Practitioners' Note is the third in a four-part series providing governments in the Middle East and North Africa (MENA) region and practitioners in the fields of social protection and disaster risk management (DRM) with general guidelines for future shock response informed by lessons learned from the COVID pandemic. It covers targeting, identification and registration, and presents recommendations focused on the best practices of MENA countries and other relevant experiences from low- and middle-income countries.
Keywords: 330; disaster risk management; COVID-19; social protection; MENA